Identifying and Classifying Small and Medium Sized Towns in Europe. (24th March 2017) - Russo, Antonio Paolo; Serrano Giné, David; Pérez Albert, Maria Yolanda; Brandajs, Fiammetta
Abstract: This paper provides a first attempt at the construction of a unified, homogeneous inventory of different classes of urban settlements in the European space, building on the approach of international institutions such as OECD and the EU in relation to larger urban areas and extending it to the specific challenge presented by smaller settlements. Its objective is twofold. The first is to address the fundamental empirical problem that was central to the development of the ESPON 2013 project 'Small and Medium sized Towns in their Functional Territorial Context' (TOWN), that is the proper geographic identification of different classes of urban settlements. The second is to introduce one basic classification of urban settlements, and two more refined typologies of small and medium sized towns (SMST). These typologies are used to provide a first impression of territorial structures of urbanisation throughout Europe, further elaborated in functional terms in the TOWN project.